Investigation of the effect of radiotherapy on the proliferative index (Ki-67) in recurring diffuse glial tumors [Nüks gösteren diffüz glial tümörlerde radyoterapinin proliferatif i̇ndeks (Ki-67) üzerine etkisinin araştırılması] - (:unkn) unknown (Ege University Press, 2011)
Introduction: Radiotherapy (RT) has various effects such as apoptosis stimulation, mitosis inhibition, mutagenic effect, chromosomal aberration and neoplastic transformation. Aim: The aim of this study was to investigate the effect of RT administered to diffuse glial tumors on the proliferation activity and mitotic activity of the tumor. Material-Method: An overall of 49 re-operated recurrent cases (16 cases had received postoperative RT while 33 cases did not receive RT) diagnosed as glial tumor were included in this study. The tumor cohort consisted of diffuse astrocytoma, oligodendroglioma and oligoastrocytomas. Ki-67 proliferating index, mitoses and grades of the primary and recurrent tumors were compared. Result: We found that the grades of recurrent tumors were lower than the grade during the first surgery in cases that had RT compared to those that had not. Similarly, Ki-67 was lower in cases that had received RT. We also noted suppressed mitotic activity in cases that had received RT.
Keywords: Glial tumors; Ki-67; Mitosis; Radiotherapy; Recurrent tumors